PEMANFAATAN KULIT BUAH DURIAN PADA PEMBUATAN ARANG AKTIF DENGAN METODE AKTIVASI FISIKA-KIMIA MENGGUNAKAN ASAM FOSFAT - Gito Christian Pane; Faizah Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The Purpose of this study was to obtain the effect concentration of phosphoric acid (H3PO4) as an activator in making of activated charcoal from durian shell. This study used a completely randomized design (RAL) with 4 treatments and 4 replications which followed by Duncan’s New Multiple Range Test at level 5%. The treatments of this research were AA1 (concentration of H3PO4 5%), AA2 (concentration of H3PO4 10%), AA3 (concentration of H3PO4 15%), AA4 (concentration of H3PO4 20%). The parameter observed were rendement, water content, ash content, volatile substance, pure carbon, and iodine adsorption. The  result of analysis showed that the variety of concentration would significantly affect rendement, water content, ash content, volatile substance, pure carbon and iodine adsorption. The chosen treatment was AA2 (concentration of H3PO4 10%) which had rendement 92.92%, water content 13.43%, ash content 7.19%, volatile substance 2.49%, pure carbon 90.31% and iodine absorption 521.93 mg/g. Keywords: activated charcoal, durian shell, phosphoric acid